2020
DOI: 10.1021/acsabm.0c00305
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Control over Cell Proliferation and Differentiation for Tissue Engineering and Regenerative Medicine Applications Using Silk Fibroin Scaffolds

Abstract: Research on tissue engineering has been actuated for want of improved treatments and has now come out as a likely alternative to organ transplantation. The two indispensable components for regeneration of tissues are cells and scaffolds. Stem cells are undifferentiated cells that have proliferative capacity and the ability to differentiate into specific mature lineages, which is called plasticity. The physical and chemical signals from the surrounding microenvironment can influence the proliferation as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 186 publications
0
13
0
Order By: Relevance
“…Silk films with carboxylic groups induced chondrogenic differentiation of human mesenchymal stem cell (hMSC), whereas those with phosphate groups induced osteogenic differentiation. Furthermore, grafting of these functional groups on silk simultaneously can provide spatiotemporal control over differentiation on the same surface (Patil et al, 2020). Surface functionalization can also be used to mimic ECM specific signaling.…”
Section: Surface Modificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Silk films with carboxylic groups induced chondrogenic differentiation of human mesenchymal stem cell (hMSC), whereas those with phosphate groups induced osteogenic differentiation. Furthermore, grafting of these functional groups on silk simultaneously can provide spatiotemporal control over differentiation on the same surface (Patil et al, 2020). Surface functionalization can also be used to mimic ECM specific signaling.…”
Section: Surface Modificationsmentioning
confidence: 99%
“…In a separate study, soft lithography was used to surface pattern SF to evaluate the effect of surface morphology on cell proliferation, orientation, and ECM alignment on corneal fibroblasts ( Gil et al, 2010 ). Interestingly, the depth of the grooves was found to have greater impact on the cell orientation compared to the width ( Patil et al, 2020 ). Patterning silk has also been harnessed to design “co-culture” systems that provide spatial control over homo- and hetero-typic cellular interactions at the micron level ( Battiston et al, 2014 ).…”
Section: Tailoring Silk Biomaterials To Control Cellular Fatementioning
confidence: 99%
See 1 more Smart Citation
“…Various species of silk worm such as Bombyx mori can be used to extract SF (70-80%) with cytocompatibility, high adhesiveness and suitable mechanical properties emanating from brillar structure with the β-sheet crystal of (Gly-Ser-Gly-Ala-Gly-Ala) n , which can promote the adhesion of platelets and proliferation of stem cells (Patil et al 2020;Anuduang et al 2020). Anti-adhesion, antiplanktonic, and inhibition of bio lm was indicated for AgNPs/gentamycin-loaded SF-based lm of titanium.…”
Section: Silk Broin (Sf) and Sericinmentioning
confidence: 99%
“…Moreover, cell differentiation begins as soon as the cells are seeded onto the array, and therefore physicochemical cues are not well suited to achieve temporal control of cell differentiation. [ 26–28 ] Recent studies have reported that myogenic differentiation and angiogenesis can be achieved through engineered optogenetics, thus allowing for spatiotemporal control of cell differentiation. [ 29 ] Although spatiotemporal control was achieved to some extent using light‐responsive recombinant cells via the implementation of gene recombination techniques, this approach exhibited several disadvantages that hindered its practical application.…”
Section: Introductionmentioning
confidence: 99%